Preferensi Siswa Sekolah Menengah Atas terhadap Pencarian Informasi Keamanan Pangan Jajanan Anak Sekolah di Jakarta - Sinaga, Martha Uli Intan Sari; Rahayu, Winiati Puji; Yanti Kamayanti Latifa (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2020)
School snack food (SSF) needs to be a priority of food safety guarantees because the consumption of SSF concerns the quality of the young generation. The method of delivering information on SSF safety is an effective way to increase awareness of food safety. This study aimed to explore the preferences of high school students for the search for food safety information. The survey was conducted to 100 SMA and MA students in DKI Jakarta; the results were processed by SPSS program using chi-square analysis. The survey results showed that 60% of students liked information from online media. Fifty percent of respondents considered the source of information as the primary consideration, and 46% believed the government was a trusted source. SMA students prioritized information sources, while MA students prioritized sources and the title of information, which were positively correlated (p